Reliable and economic operation of regional-community integrated energy systems: A hybrid game approach based on state similarity - Qu, Jiawei; Xu, Kaiwen; Hou, Kai; Liu, Zeyu; Wu, Hao; Jia, Hongjie; Zhu, Lewei (Energy (Oxford), 2025)
The reliability of Regional Integrated Energy Systems (RIES) and Community Integrated Energy Systems (CIES) is a prerequisite for continuous high-quality energy supply. However, optimizing multi-agent operations for RIES and multi-CIESs based on optimal energy flow remains challenging, especially under fault scenarios. To address this, a Reliable Economic Operation model for RIES and Multi-CIESs (REO-RMC) is proposed. This model ensures the reliable operation of RIES and CIES through a hybrid strategy of Stackelberg and cooperative games while optimizing the operation of multi-CIESs and achieving optimal profit distribution. To improve the efficiency of the hybrid game, a State Similarity (SS) method is proposed. The SS method converts uncertainties (such as renewable energy and energy prices) in the linear parts of REO-RMC into parameter fluctuations within multi-parameter programming, constructing critical regions (CR). Subsequently, equation solving replaces the optimization process for all problems within the CR, improving computational efficiency. Moreover, a framework for Offline CR Generation and Online CR Identification (OGOI) is proposed to further enhance efficiency. Results show that the REO-RMC framework effectively enhances the economic operation of the CIES alliance while ensuring the reliability of RIES. Furthermore, the SS method reduces computation time to less than 50 % of that required by bilevel-programming. •A reliable economic operation model for RIES and multi-CIESs.•A hybrid game strategy combining Stackelberg and cooperative games.•A state similarity method for rapid Stackelberg game resolution.•A framework for offline CR generation and online identification.